(untitled) (Intent Research Scientific Journal, 2023)
Starting from the generally accepted views, according to which each language has its own peculiarities of reflecting the picture of the world, linguists also distinguish a number of features and characteristics for the English language. In this case, it is legitimate to talk about the English language picture of the world; this has its own cultural dominants that differ from other languages.